2021
DOI: 10.1177/09603271211033768
|View full text |Cite
|
Sign up to set email alerts
|

MiR-141 attenuates sepsis-induced cardiomyopathy by targeting DAPK1

Abstract: Objective To discuss the possible effects of microRNA-141 (miR-141) in sepsis-induced cardiomyopathy (SIC) via targeting death-associated protein kinase 1 (DAPK1). Methods An SIC mouse model was constructed by abdominal injection of lipopolysaccharide (LPS) and divided into control, LPS, LPS + pre-miR-141, and LPS + anti-miR-141 groups. Hemodynamic indicators and heart function indexes of mice were detected. ELISA was used to determine the serum levels of inflammatory cytokines, while TUNEL staining to observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Our study found that LC3B and Beclin1 were upregulated and p62 was downregulated after knockdown of DAPK1 in JEG‐3 cells. Lipopolysaccharide‐induced SIC models were constructed to investigate the role and mechanism of miR‐141‐targeted DAPK1 in SIC, which found that miR‐141 could decrease the inflammatory response and reduce the apoptosis of myocardial cells through downregulating the expression of DAPK1 in SIC (Song et al, 2021). Considering the significance of DAPK1 in Alzheimer's disease (AD) and its target relationship with miR‐130a‐3p, Wang et al hypothesized that miR‐130a‐3p could improve cognitive function in AD through targeting DAPK1 (Wang, Shi, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that LC3B and Beclin1 were upregulated and p62 was downregulated after knockdown of DAPK1 in JEG‐3 cells. Lipopolysaccharide‐induced SIC models were constructed to investigate the role and mechanism of miR‐141‐targeted DAPK1 in SIC, which found that miR‐141 could decrease the inflammatory response and reduce the apoptosis of myocardial cells through downregulating the expression of DAPK1 in SIC (Song et al, 2021). Considering the significance of DAPK1 in Alzheimer's disease (AD) and its target relationship with miR‐130a‐3p, Wang et al hypothesized that miR‐130a‐3p could improve cognitive function in AD through targeting DAPK1 (Wang, Shi, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%